Deskripsi Pencapaian Perkembangan Bahasa Asing pada Anak Usia Dini Kelompok B di TK Nurul Ilmih Kecamatan Lakea Kabupaten Buol - Cindi A Kalamunting; Rapi Us. Djuko; Nunung Suryana Jamin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study is a scholarly work by a student of the Early Childhood Education Teacher Education Program, Faculty of Education, Universitas Negeri Gorontalo, supervised by Dra. Rapi Us. Djuko as the first advisor and Mr. Nunung Suryana Jamin, SE, M.Si as the second advisor. The objective of this research is to provide a comprehensive overview of foreign language development achievements among early childhood learners in Group B at TK Nurul Ilmih. The study adopts a qualitative descriptive approach, utilizing observation, in-depth interviews, and documentation as data collection methods. A total of 22 children participated as the primary subjects and were actively involved throughout the observation process. The research focused on several linguistic aspects, including language comprehension, verbal expression, basic vocabulary usage, pronunciation ability, and children's responses to bilingual instructions (in both Indonesian and English). The findings indicate that the children’s foreign language development falls within the